PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DENGAN MENGGUNAKAN MEDIA MODUL DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN AKUNTANSI PADA SISWA SMA SE-KOTA BANDUNG - Purnamasari, Imas; Tanuatmodjo, Heraeni; Yuliyanti, Leni (Jurnal Riset Akuntansi dan Keuangan, 2014)
The results of student learning is a combination of various factors that affect the overall learning process. The phenomenon in this study is the lack of student learning outcomes are seen from the results of the national exam on economic subjects, especially the material accounting, one of the causes of the problems in the learning process, namely on how to give lessons conducted by teachers, and the use of instructional media, especially the media module.This study, use the method of the experiment to make a difference between the results of the study on the student teaching and learning by contextual the use of the media, the students are not using the models of the contextual teaching and learning to use media. Results of the analysis of 10 schools in the city of bandung at 8 school with the influence of contextual teaching and learning module, using this hypothesis can be seen from the increase is the result of study to students.